The impact of response rate on Hospital Consumer Assessment of Healthcare Providers and System (HCAHPS) dimension scores - Erin Godden; Andrea Paseka; Jan Gnida; Joe Inguanzo (The Beryl Institute, 2019)
Patient experience measurement is receiving considerable attention from hospital executives, healthcare leaders, purchasers such as the Centers for Medicare and Medicaid Services (CMS), and patients. It is therefore appropriate and necessary to examine the methods of survey administration, and the analysis presented here seeks to understand the impact of one particular aspect of the measurement: response rate. Utilizing publicly reported HCAHPS (Hospital Consumer Assessment of Healthcare Providers and Systems) data from Hospital Compare, a positive correlation between response rate and HCAHPS scores nationwide was identified and replicated. This correlation, which was most recently published by the Hospital Quality Institute (HQI) for California facilities, implies that increasing response rates can return higher HCAHPS dimension scores. Accurate patient perceptions of the inpatient experience may be hidden by insufficient representativeness of the data. In other words, publicly-reported scores may be lower than they should be, and hospitals may be mistakenly devaluing their efforts to improve the patient experience. Responses from a more representative sample of the patient population are key to capturing more accurate HCAHPS scores.